Sorghum (Sorghum bicolor L.) grain yield response to contour-based rainwater harvesting and organic fertilizer in rainfed farming systems - Friday Nguvayasvika Mudondo Kubiku; Ronald Mandumbu; George Nyamadzawo (Cogent Food & Agriculture)
Rainfall variability and low soil fertility are negatively affecting sorghum grain yield in smallholder farming systems. This study investigated the effect of contour-based rainwater harvesting (RWH) systems and cattle manure on grain yield of two sorghum varieties Macia and Sc Sila. A factorial experiment was laid out in a split-split plot design and replicated three times. Rainwater harvesting practice (tied contour, infiltration pits, standard contour) were the main plot factor, sorghum variety (Macia, Sc Sila) sub-plot factor, cattle manure application rates (0; 5; 8; 10; 15; 20) t/ha sub-sub plot factor, and distance from rainwater harvesting practice (0–5 m; 5–10 m; 10–15 m) sub-sub-sub plot factor. Grain yield under tied contour (TC) and infiltration pits (IP) rainwater harvesting systems were compared with the control - standard contour (SC). The results showed that TC and IP improved soil moisture content by 1.83% and 1.71% respectively compared to SC. Sorghum grain yield was significantly higher (p < 0.05) under TC and IP at all cattle manure application compared with SC. Grain yield significantly differed (p < 0.05) in the order TC (2.51 t/ha) > IP (2.10 t/ha) > SC (1.49 t/ha) at cattle manure application rate of 20 t/ha. Sorghum variety Macia had the highest grain yield of 2.01 t/ha at cattle manure application of 20 t/ha. In both sorghum varieties, TC and IP had higher sorghum grain yields than SC at all distances from the RWH practice in both seasons (2016/17 and 2017/18). The findings suggest that the use of TC and SC RWH practices, and cattle manure may increase sorghum grain yields in rain-fed smallholder farming systems.